2023
DOI: 10.1126/sciadv.adf0405
|View full text |Cite
|
Sign up to set email alerts
|

Gaze following in Archosauria—Alligators and palaeognath birds suggest dinosaur origin of visual perspective taking

Abstract: Taking someone else’s visual perspective marks an evolutionary shift in the formation of advanced social cognition. It enables using others’ attention to discover otherwise hidden aspects of the surroundings and is foundational for human communication and understanding of others. Visual perspective taking has also been found in some other primates, a few songbirds, and some canids. However, despite its essential role for social cognition, visual perspective taking has only been fragmentedly studied in animals,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…One further way of inferring cognitive traits in dinosaurs is by comparatively studying relevant behavioral phenomena in living crocodylians and birds, the groups that form their extant phylogenetic bracket. While such approaches are starting to gain pace (Zeiträg et al, 2023), we are not aware that ethological research could so far identify shared physical or social cognitive skills in crocodylians and birds that have not also been found in turtles and squamates (in case comparative data is indeed available - Zeiträg et al, 2022; Font et al, 2023). Thus, the behavioral resolution of such approaches appears limited thus far.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One further way of inferring cognitive traits in dinosaurs is by comparatively studying relevant behavioral phenomena in living crocodylians and birds, the groups that form their extant phylogenetic bracket. While such approaches are starting to gain pace (Zeiträg et al, 2023), we are not aware that ethological research could so far identify shared physical or social cognitive skills in crocodylians and birds that have not also been found in turtles and squamates (in case comparative data is indeed available - Zeiträg et al, 2022; Font et al, 2023). Thus, the behavioral resolution of such approaches appears limited thus far.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 99%
“…Cognitive traits found exclusively in birds or crocodylians cannot simply be extrapolated to Mesozoic dinosaurs with any degree of certainty since they might be crown group apomorphies. Whereas it might be appealing to hypothesize that cognitive patterns found among modern palaeognaths are representative for their maniraptoriform forerunners (Jensen et al, 2023;Zeiträg et al, 2023), this idea is (in most cases) not testable and should hence not be disseminated uncritically.…”
Section: ) Inferring Life History Traitsmentioning
confidence: 99%
“…While discussed here only for primates, MENA processes could be more evolutionarily widespread and also relevant to predators. Various mammals like dolphins [49], horses [50] and wolves [51], and some birds like emus, rheas and tinamous [52], understand others' perspectives, suggesting "visual perspective taking, with accompanying representations of gazes' referentiality, evolved earlier in dinosaurs" [52]. Both prey and predator behaviour involve perceiving attention and eyes.…”
Section: Actmentioning
confidence: 99%
“…Evidence supporting this view has found that gaze-triggered social attention is reflexive [ 13 , 14 ], independent of consciousness [ 15 , 16 ], and heritable [ 17 ]. Moreover, various nonhuman animals, such as apes [ 18 ], monkeys [ 19 ], wolves (and dogs) [ 20 , 21 ], and birds [ 22 , 23 ], exhibit a similar social attention ability. The accumulating evidence suggests that this ability may be “hard-wired” in the vertebrate brain, similar to the predisposition to attend to face and biological motion [ 24 ].…”
Section: Introductionmentioning
confidence: 99%